Incidence, clinico-demographic profiles and survival rates of colorectal cancer in Northern Malaysia: Comparing patients above and below 50 years of age - Ibrahim N.R.W.; Chan H.-K.; Soelar S.A.; Azmi A.N.; Said R.M.; Hassan M.R.A. (Asian Pacific Organization for Cancer Prevention, 2024)
Indexed by Scopus/ERA